Therapeutics with SPION-labeled stem cells for the main diseases related to brain aging: a systematic review - Alvarim LT (Dove Medical Press, 2014)
Larissa T Alvarim,1,3,* Leopoldo P Nucci,2,* Javier B Mamani,1 Luciana C Marti,1 Marina F Aguiar,1,2 Helio R Silva,1,3 Gisele S Silva,1 Mariana P Nucci-da-Silva,4 Elaine A DelBel,5,6 Lionel F Gamarra1–31Hospital Israelita Albert Einstein, São Paulo, Brazil; 2Universidade Federal de São Paulo, UNIFESP, São Paulo, Brazil; 3Faculdade de Ciências Médicas da Santa Casa de São Paulo, São Paulo, Brazil; 4Departamento de Radiologia, Hospital das Clínicas, Universidade de São Paulo, Brazil; 5Universidade de São Paulo-Faculdade de Odontologia de Ribeirão Preto, São Paulo, Brazil; 6NAPNA- Núcleo de Apoio a Pesquisa em Neurociências Aplicadas, São Paulo, Brazil*These authors contributed equally to this workAbstract: The increase in clinical trials assessing the efficacy of cell therapy for structural and functional regeneration of the nervous system in diseases related to the aging brain is well known. However, the results are inconclusive as to the best cell type to be used or the best methodology for the homing of these stem cells. This systematic review analyzed published data on SPION (superparamagnetic iron oxide nanoparticle)-labeled stem cells as a therapy for brain diseases, such as ischemic stroke, Parkinson’s disease, amyotrophic lateral sclerosis, and dementia. This review highlights the therapeutic role of stem cells in reversing the aging process and the pathophysiology of brain aging, as well as emphasizing nanotechnology as an important tool to monitor stem cell migration in affected regions of the brain.Keywords: iron oxide, dementia, stem cell, stroke, Parkinson’s disease, sclerosis disease, brain aging